Perancangan Sistem Inventory Bara Di CV.Madani Sportware Menggunakan Metode Incremental Berbasis Web - Hafidsyah eka prayogi ogi; Moehammad Al Irfan; Wasis Haryono (CV. Multi Kreasi Media, 2022)
Madani Sportwear is engaged in the production and convection of various jerseys (ball, futsal, badminton, bicycle), or sports shirts, t-shirts, polo shirts, jackets, and the manufacture of Digital Printing Services and other production goods. The problem that occurs in the system that is currently running is the recording and management of goods in and out (inventory) so as to make the company's performance slow. Although already have computer facilities, but in CV. Madani Sportwear still uses manual note-taking using the Ms. Excel, there is no effective application for quick and efficient inventory of goods. Therefore, to facilitate the recording and management of incoming and outgoing goods, we need a web-based inventory system that will be made by the author based on the existing system in CV. Madani Sportwear. In addition to the process of exiting and entering goods, this system is also equipped with features of requesting goods and searching for goods based on the name and code of the goods. With the goods inventory system that we have created, it can be useful and used for related companies to implement the design. This system is built using PHP programming language, database using MYSQL, and mockup design with Balsamiq Wireframe. And for the system design method using the Incremental method as system analysis and design.